2023
DOI: 10.1111/ejn.16179
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity occurs in a specific phenotype of neurons in the nucleus tractus solitarius of dystrophin gene‐mutated rats

Akitoshi Chikamoto,
Ryota Tochinai,
Shin‐ichi Sekizawa
et al.

Abstract: Duchenne muscular dystrophy (DMD) is a severe progressive neuromuscular disorder that causes cardiac and respiratory failure. Patients with DMD have tachycardia and autonomic nervous dysfunction at a young age, which can potentially worsen cardiorespiratory function. Therefore, we hypothesised that plasticity occurs in neurons of the cardiorespiratory brainstem nucleus (nucleus tractus solitarius [NTS]) due to DMD, thus affecting neuronal regulation because afferent information from cardiorespiratory organs ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A prospective study reported an adolescent developing cardiomyopathy while on eteplirsen, consistent with DMD's typical progression [ 27 ]. It has also been shown that DMD is associated with an increased likelihood of cardiac events [ 28 ]and can precipitate respiratory failure [ 29 ]. Whether the causative factors behind these complications are inherent to the disease itself or are triggered or exacerbated by the medication deserves further investigation We call for vigilance in these adverse effects of concern so that appropriate preventive measures can be taken.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study reported an adolescent developing cardiomyopathy while on eteplirsen, consistent with DMD's typical progression [ 27 ]. It has also been shown that DMD is associated with an increased likelihood of cardiac events [ 28 ]and can precipitate respiratory failure [ 29 ]. Whether the causative factors behind these complications are inherent to the disease itself or are triggered or exacerbated by the medication deserves further investigation We call for vigilance in these adverse effects of concern so that appropriate preventive measures can be taken.…”
Section: Discussionmentioning
confidence: 99%